Effect of Yoga and Naturopathy Interventions among Alcohol Addicts - R, Subbiah; R, Anusha; S, Prashanth (Indian Journal of Integrative Medicine, 2025)
Alcoholism is a prevalent and deadly illness that is linked to mental health issues. Heavy drinking throughout adolescence harms a developing brain and may cause cognitive issues in later life. Symptoms of alcohol withdrawal syndrome usually include headache, nausea, hallucinations, sleeplessness, and moderate anxiety. Ten men between the ages of 30 and 50 who had a history of alcohol addiction for the previous five years were diagnosed using the AUDIT scale according to DSM-5 criteria. As part of their rehabilitation, they received yoga and naturopathy treatments such as mud packs, gastro-hepatic packs (GH packs), acupuncture, aroma oil head massages, gibberish meditation, and relaxation techniques for ten consecutive days. This study was designed as pre- and post-data collection and the paired samples t-test revealed a statistically significant difference (p